Perspectivas y polos de desarrollo en América Latina - Grabendorff, Wolf (Estudios Internacionales, 1980)
It is very difficult to make an evaluation of the changes that may have occurred in Latin America’s bargaining power vis-à-vis the rest of the world. Reference is made here to events that have occurred in the international economy and have modified the region’s "negotiating capacity", as well as the way it is inserted in the world. For this, the work is divided into a first section destined to review what has been the evolution of the Latin American economies and the way in which the way of thinking about the development process has been modified. Then the most important events, from a negotiation perspective, that have taken place are presented. At the end, a balance is made of the elements that should be considered to analyze the degree of regional autonomy in its global insertion.